[Image 41] - Smith, Captain Sir William [?ob. 1732] (My University, 1803)
Captain Sir William Smith was in the Royal Engineers.
Original drawings and paintings of Ireland and Scotland, vol 1
View of the remains of an Old Castle supposed to be one of O'Doghertys 4 miles from Londonderry and 28 from Birdstown drawn by Sir. Wm Smith in 1802.
Keywords: O Dochartaigh Clann; Doherty; Fortification; Architectural drawings; Ireland -- Antiquities -- Pictorial works; Castles in art; Londonderry (Northern Ireland : County); Ulster (Northern Ireland and Ireland)